Enzyme-linked immunospot assay and metagenomic sequencing of Mycobacterium tuberculosis, coagulopathy symptoms, and pancytopenia testing for characterization of pulmonary tuberculosis: case report and literature review: ELISPOT and mNGS of MTB for pulmonary tuberculosis - Liu, Helei; Xia, Hong; Jia, Bei; Wu, Jing (Cellular and Molecular Biology, 2022)
Pulmonary Tuberculosis (TB) is common in China, but tuberculosis with coagulation disorders and pancytopenia have rarely been reported in the past. In this report presented, a 70-year-old female was admitted to the hospital with poor appetite, dark urine, nausea, vomiting, fatigue, and bilateral lower limb edema; chest CT suggested diffuse infectious lesions in both lungs, coagulation dysfunction, and complete pancytopenia, which was initially considered to be caused by severe infection. However, the patient's symptoms did not improve by potent empiric antibiotics treatment, and a repeat chest CT showed that the lung lesions deteriorated more than before, and coagulation disorders and pancytopenia did not improve. Finally, the TB patient tested positive for enzyme-linked immunospot assay (ELISPOT) and metagenomic sequencing (mNGS) of Mycobacterium tuberculosis (MTB) using bronchoscopic alveolar lavage. So ati-TB was initiated with HRftELfx (isoniazid, 0.3 g qd; rifapentine, 0.45 g biw; ethambutol, 0.75 g qd; and levofloxacin, 0.5 g qd) regimen. Eventually, the patient's clinical symptoms improved significantly, the pulmonary lesions were absorbed, and the coagulation function and blood cell count returned to normal, which achieved a satisfactory treatment effect.